Jordan throughout Civilizations - Jarrar, Amani G (RIRAI Publisher, 2025)
This study explores the historical evolution of Jordan throughout various civilizations, highlighting its role as cultural crossroads and strategic hub in the ancient and modern worlds. From prehistoric settlements to the rise of Canaanite, Nabataean, Roman, Byzantine, and Christian then Islamic civilizations, Jordan has continuously contributed to the shaping of regional identity and heritage. The research utilizes a historical-analytical methodology to trace the development of political, social, and cultural structures on Jordanian soil, emphasizing the continuity and transformation of governance, religious tolerance, and civilizational interaction. The study also sheds light on Jordan’s transition into a modern state under Hashemite leadership, grounded in the principles of the Great Arab Revolt. It underscores the Kingdom's current role in promoting peace, dialogue, and moderate governance in the Middle East. Additionally, the research reflects on the significance of Jordan’s Vision 2025 as a blueprint for national development, citizen empowerment, and sustainable progress. Ultimately, Jordan emerges as a model of continuity between past and present, leveraging its historical legacy to construct a forward-looking national identity rooted in stability, openness, and civilizational depth.